Memorandum of Understanding between Universiti Teknologi MARA, Malaysia and Universitas Pembangunan Nasional Veteran Jakarta on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel/student exchange - Cawangan Kelantan, UiTM (2022)
This Memorandum of Understanding (hereinafter referred to "MoU") is executed on the 19th day of September 2022 between Universiti Teknologi MARA (hereinafter referred to as "UiTM"), a public university established under the Universiti Teknologi MARA Act 1976 whose address is at Chancellery, Universiti Teknologi MARA, 40450 Shah Alam, Selangor Malaysia and Universitas Pembangunan Nasional 'Veteran' Jakarta (hereinafter referred to as "UPNVJ"), an institution of higher learning whose address is at Jalan RS. Fatmawati No. 1, Pondok Labu, Jakarta Selatan 12450, Indonesia and shall include its lawful representatives and permitted assigns; UiTM and UPNVJ shall hereinafter referred to singularly as "the Party" and collectively as "the Parties".